Ayurvedic Management of Cholelithiasis (Pittashmari) – A CaseStudy - Gupta, Aman; Gupta, Monika (International Research Journal of Ayurveda & Yoga, 2024)
Gallstone formation, or cholelithiasis, is caused by a number of factors, including supersaturation of bile with cholesterol, accelerated nucleation of cholesterol monohydrate in bile, bile stasis, or delayed gallbladder emptying due to impaired gallbladder motility. After carefully rewriting Ayurvedic scriptures, we find that, because of its resemblance in location and function, the bile secreted from the gallbladder can be compared to the Accha Pitta stated in Ayurveda. We report that a case of cholelithiasis (Pittashmari) in a 31-year-old female patient had been complaining of severe abdominal pain, distension of the abdomen, and vomiting. Oral medications such as Arogyavardhini vati, tablet Trikatu, Kashaya of Trivrit, Katuki, Sanaya, Arghvad, and Daruharidra were administered to the patient for 3 months. A significant response was observed over clinical symptoms and USG reports. Ayurvedic remedies were used to treat the patient for 3 months. This case study demonstrates the efficacy of Ayurvedic treatment for cholelithiasis (Pittashmari). The study reached the conclusion that Ayurvedic therapy was significantly effective in the treatment of cholelithiasis (Pittashmari).